Analisis Kemampuan Pemecahan Masalah Matematis Siswa dalam Menyelesaikan Soal Perkalian dan Pembagian Bilangan Rasio Kelas VII di SMP Negeri 1 Kota Tambolak - Nendur, Elda Rambu; Cordia, Misseri Grassiana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the mathematical problem solving ability of grade VII-F students of SMP Negeri 1 Tambolak City on integer material using the Problem Based Learning (PBL) learning model. This research is qualitative descriptive research. Data collection techniques use tests and observation of students' ability to solve questions and interviews. Analysis of students' mathematical problem-solving skills using polya work steps. The results of data analysis show that the application of the Problem Based Learning (PBL) learning model can improve students' mathematical problem solving skills on class VII integer material at SMP Negeri 1 Tambolaka City. This can be seen when students solve a given problem, students understand the problem, then plan and implement the plan and write down the answer step by step using the appropriate and precise formula. In addition, students explain answers with appropriate reasons. However, there are some students who do not meet the first and fourth indicators, namely rewriting what is known, being asked from the question and looking back at the answers.